An examination of Rand Water's skills development for the production of quality drinking water locally - Govender, Esthelyn Carol (My University, 2016)
The study investigates the effectiveness of Rand Water’s Scientific Services’ skills development strategy for the assurance of quality drinking water as prescribed by the SANS 0241 National Drinking Water Quality Standard. The aim is to establish whether: 1) the present skills are adequate to provide the scientific data required for affirming drinking water quality and 2) the skills development taking place in the Scientific Services division is adequate for the level and quantity of scientific skills required for the future. There is also some discussion to understand the motivation for maintaining and increasing skills within the Scientific Services division for Rand Water. Assuring drinking water quality within Rand Water is the sole responsibility of the Scientific Services division. The division provides regular routine and non-routine drinking water quality monitoring, testing, data collection, analyses and reporting on the organisation’s performance against the SANS 0241 Drinking Water Quality Standards (SANS, 2006).The focus of the analysis is Scientific Services Division in Rand Water, although the discussion in view of the topic is not limited to the division. Production of drinking water encompasses two key aspects that must be investigated they are quality and quantity, however the close up analyses could only be successful completed for quality in the context of the quantity produced. Skills development planning within Scientific Services has always been based on the division’s feeder pipelines to be able to recruit from and retain scientific skills within the organisation. The division concentrates on Graduate, Bursar and Experiential Learner development ensuring a sustainable, trained and readily available pipeline of skills from which to recruit. Employees currently within the division both permanent and temporary form the type of scientific skills required for water quality monitoring and drinking water standard production and assurance. Employees have been placed within the functional scientific streams of the division and further by their levels of appointment and qualifications. The data analysis has also been done for the increasing of skills using the same framework. Age and gender was also included to show performance of the division in respect to transformation and equity. Equity in relation to growth is currently a global matter that is under scrutiny. The World Economic Forum has put equity in the spotlight to ensure countries look at their performance. The significance is that it has an impact on how the water resources in a country are distributed and managed. The Water Reforms in most developing countries have sparked large scale discussions around provisioning of water for all. Human Development and Water Resource Management are agendas that countries need to handle collectively with the ultimate outcome being achieving equity for all (UNDP, 2013). Rand Water’s Scientific Service skills data indicates that it has adequate scientific capacity to meet its present mandate of providing drinking water quality assurance for the organisation. There is some concern that the aging workforce is concentrated at management and specialists levels, therefore developing these skills for the next 5 to 10 years requires immediate attention. Transfer of skills and retention of skills requires careful strategic planning in order to attract a younger transformed workforce. The study shows that in as much as routine quality assurance is core, it is also equally critical to have employees who can troubleshoot within the context of the new environmental pressures and diverse operational conditions. The demand for quality drinking water over the last 110 years has increased throughout the country. The mandatory expansion of the organisation translates into sharing of human resources with other parts of the country to produce quality drinking water. Rand Water has been entrusted to take on the responsibility of other water utilities in the country and ensure that they reach the required standard for the production of quality drinking water. The full scope of the organisation’s mandate requires that it provide skills to handle the treatment of drinking water and wastewater in the near future. Although wastewater treatment is currently managed by the local municipalities, Rand Water will be having an active role to improve services. This would mean distributing the existing capacity within the organisation over a greater area of work along with a significant increase in the demand for scientific analyses of drinking water quality. The pace at which skills development takes place in Rand Water Scientific Services division shows that it will be able to meet the present needs. There are questions raised on the sustainability of the skills for the future. Maintaining and developing skills within the division is critical to be able to sustain the nature, structure and functioning of the division in its current form. The other factor that must also be maintained is the transformational equity demands of the country. The notion that there is a lack of experienced previously disadvantages scientists must be addressed directly to meet all the future demands of the sector, region and continent in a short space of time.
A research report submitted to the Faculty of Engineering an the built environment, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, October 2016.
Keywords: Drinking water--South Africa; Water quality management--South Africa; Water resources development